2001
DOI: 10.1029/2000gl012007
|View full text |Cite
|
Sign up to set email alerts
|

A new type of sea bed waves

Abstract: Abstract. Sandy beds of shallow tidal seas often exhibit a range of rhythmic patterns, from small-scale ripples a few metres long to large tidal sandbanks with a wavelength of kilometres. For example, on the access route to Rotterdam harbour ships cross a field of sandwaves. The crests of these sandwaves determine the effective navigation depth. To warrant navigability, the North Sea Directorate of the Netherlands Ministry of Transport, Public Works and Water Management continually monitors the bathymetry in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
42
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 10 publications
0
42
0
1
Order By: Relevance
“…The results previously described have been obtained by fixing those related to the site on the basis of the field measurements described in Knaapen et al (2001) If the tidal strength is fixed at U * 0 = 0.6 ms −1 and the ellipticity is varied, both clockwise and counterclockwise long bed waves form when e is larger than about 0.2, up to almost circular tides. Finally, runs have been made using the sediment transport rate formulations of Meyer-Peter & Muller (1948) and Soulsby and Van Rijn (Soulsby 1997) instead of that proposed by Fredsøe & Deigaard (1992).…”
Section: Robustness Of the Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results previously described have been obtained by fixing those related to the site on the basis of the field measurements described in Knaapen et al (2001) If the tidal strength is fixed at U * 0 = 0.6 ms −1 and the ellipticity is varied, both clockwise and counterclockwise long bed waves form when e is larger than about 0.2, up to almost circular tides. Finally, runs have been made using the sediment transport rate formulations of Meyer-Peter & Muller (1948) and Soulsby and Van Rijn (Soulsby 1997) instead of that proposed by Fredsøe & Deigaard (1992).…”
Section: Robustness Of the Resultsmentioning
confidence: 99%
“…By analysing bathymetric surveys made in the North Sea, Knaapen et al (2001) have identified new bedforms which can be classified neither as sand waves nor as sand banks. These new bedforms, named long bed waves, are characterized by crests which are 60…”
Section: Introductionmentioning
confidence: 99%
“…Subaqueous dunes are bedforms produced in river channels, estuaries, and coastal zones [1][2][3]. They are formed with different sediment sizes, mostly ranging from medium sand to gravel [4], and show rhythmic patterns caused by the interaction of turbulent flow on the riverbed [5].…”
Section: Introductionmentioning
confidence: 99%
“…2014; Knaapen et al, 2001). Esses refletores geralmente não possuem continuidade lateral, porém, podem apresentar regularidade e padrão de refletividade devido à influência adquirida pelo contato com outras unidades estruturais ou pelo comportamento constante de fluxo havendo poucas alterações em um longo período de atuação (Harvey et al, 2005;Miall, 2006), além de apresentar desconformidades, assimetria e configuração caótica em sua disposição, o qual é comportamento característico de ambientes energéticos com variações abruptas de dinâmica e de forçantes de deformação do processo de sedimentação (Bourgoin et al, 2013;Wittmann et al, 2011), nota-se uma tendência de inclinação de alguns refletores de NW-SE, levando a crer que essas formas de fundo estão se deslocando perpendicularmente a direção do Canal do Norte com transporte de carga de fundo aparente para a montante (Besio et al, 2008;Komarova and Newell, 2000;Strasser, 2008 (Baas et al, 2016;Neill et al, 2012).…”
unclassified